EXPLORING COHESIVE DEVICES IN SEVENTH-GRADE ENGLISH TEXTBOOKS: A DISCOURSE ANALYSIS - Riska Nurul Fitriani; Aliva Rosdiana (University of Kuningan, 2025)
English textbooks serve as crucial instructional resources in Indonesian EFL contexts, with cohesive devices like conjunctions playing a vital role in text comprehension. Despite extensive research on cohesion, seventh-grade textbooks remain underexplored, particularly in Indonesia. This study analyzes conjunction types (additive, adversative, causal, temporal) and their functions in a seventh-grade English textbook to evaluate their role in enhancing coherence and pedagogical effectiveness. A qualitative descriptive approach was employed, examining 13 texts from